Tensiometric, fluorescence and 1H NMR study of mixed micellization of non-steroidal anti-inflammatory drug sodium salt of ibuprofen in the presence of non-ionic surfactant in aqueous/urea solutions. (May 2016) - Rub, Malik Abdul; Khan, Farah; Sheikh, Mohmad Shafi; Azum, Naved; Asiri, Abdullah M.
Highlights: Interaction between (IBF + TX-100) mixtures has been investigated. (IBF + TX-100) mixtures exhibit synergistic behavior. Urea increases the surface charge of the micelles resulting halt of the micelles formation. N agg, K sv and dielectric constant of mixed systems have also been evaluated. 1 H NMR data suggested that IBF and TX-100 interacts through hydrophobic as well as hydrophillic interaction. Abstract: The desirable surface/bulk properties for specific applications of drug sodium salt of ibuprofen (IBF) and Triton X-100 (TX-100) can be achieved by adjusting mainly the composition of these systems. The interactions of anionic drug IBF with non-ionic surfactant TX-100 micelles have been investigated using tensiometry, fluorometry and 1 H NMR in aqueous as well in 250 mmol⋅kg −1 urea solutions. Different theoretical models like Clint, Rubingh, and Rosen, etc. were utilized to get information about the nature of interaction between these two in bulk and at the interface. These models disclose that the non-ideal behavior with attractive interaction in bulk and at the interface exists. The steady-state fluorescence quenching study was employed to evaluate micelle aggregation numbers ( N agg ), which signify the involvement of surfactant was forever higher compared to IBF. Stern–Volmer binding constants ( K sv ), micropolarity ( I 1 / I 3 ) and dielectric constant ( D exp ) of the mixtures are also obtained using fluorescence method. By the addition of urea raise in the surface charge of the micelles was observed followed by halt of the micellization of drug and surfactant as well as their mixture, therefore cmc values increases followed by decrease in aggregation number. The 1 H NMR resonance intensity variations were paralleled by upfield shifts in the resonance frequencies, due to an increased shielding of IBF happening from closeness of the non-ionic TX-100 surfactant.